Law Enforcement Against Traffic Law Violations Committed by Students in Ternate City - Fahria, Fahria; Djafar, Muhammad Mufti M; Muhdar, Gamar; Budiono, Arief (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Traffic rules are created to guard the safety of everyone who travels on vehicles on the road every day. Rampantly occurring traffic violations that evoke concerns in society are traffic violations committed by students. This paper aims to analyze the factors that influence law enforcement against traffic law violations committed by students in the legal area of the Ternate City Police Resort Traffic Unit as well as the efforts carried out to prevent events of traffic law violations by students. This research used the empirical research design. It was an approach model in the form of an action to see the legal reality in society. In this research, the researchers collected the data using field research, literary study, and documentation methods. From these three types of data collection, the data obtained were divided into two, namely primary and secondary data. Research found that the factors which influence law enforcement against traffic law violations committed by students in the legal area of Ternate City Police Resort Traffic Unit are the family factor, the education factor, and the environmental factor. Legal efforts that may be applied to prevent the occurrence of traffic law violations committed by students in the legal area of Ternate City Police Resort Traffic Unit are: (1) Preventive efforts, by organizing socializations especially for parents to always supervise their children and prevent them from driving motorized vehicles as underage children are not eligible to obtain a driver’s license, as according to the law, a person must be at least 17 years old to obtain it and (2) Repressive efforts by giving a warning to students that violate the traffic laws. If perpetrators still commit violations after obtaining a warning, they will obtain a ticket